Um império transviado em Sodoma : uma genealogia queer da sodomia e do sodomita no Império Português - séculos XVI-XVIII - Cássio Bruno de Araujo Rocha (2021)
The thesis aims to produce a queer genealogy of sodomy and sodomites, exploring them as a theological concept, a category of subjectivity or an erotic practice. The scenario of the research is the Portuguese Overseas Empire during the Modern Age, in the midst of the persecutory action of the Holy Office of the Inquisition. The central problem is to discern in which discursive and extra discursive conditions the sodomite could function as a category of subjectivity. The knowledge-power relations correspond to, respectively, those discursive and non-discursive conditions. Its play outlined, on these societies, a mode of experience of eroticism typically Christian. In the wake of the last Foucault, this work denominates this Christian mode of experience of the erotic as the dispositif (device or apparatus) of the flesh, in whose bosom, certain subjects were interpellated (subjected and subjectified) and, thus, manufactured. Thereby, the thesis constitutes itself by three focuses of an arqueo-genealogical analysis, originating the three Parts of the text. One facing the knowledge relations around sodomy and the sodomite as categories organized in certain discursive formations. Another interested in the power relations capable of interpellate people adept of homoeroticism and/or anal eroticism as subjects sodomites or Christians. In addition, a third one directed to the ways that the subjects went on making themselves up in the whirlwind of the knowledge-power relations and the wider historical processes in the Old Regimen, colonial and slavery societies. How did the practices of subjectivation of the sodomite subjects come to be in the midst of the experience of the Christian flesh? Sources like the inquisitorial lawsuits (as well as the denunciations and confessions registered in the Cadernos do Nefando) stored up narratives about the lives of people who practiced some form of sodomy. They were the basis from which to question how both sodomy and the sodomite became discursive and non-discursive objectives in three levels. First, the moral and spiritual problematization by the Catholic Church. Second, the efforts of government of the souls of the subjects of the Portuguese Empire, whose institutions sought to create a political fantasy of a unified confessional Christian and chaste Empire. Third, the everyday practices of subjectivation acted up by homoerotic lovers and/or connoisseurs of anal sex. Lastly, the thesis aims to dislodge contemporary categories of sexual identity, through focus on the historical discontinuities between homosexuality and sodomy. What was the radical historical specificity of those subjects that were seen as such a terrible menace, that it was capable of turning Portugal into an Empire perverted into Sodom? Theundisputable otherness of the sodomite, this juridical subject condemned to the maximum penalties in hell for his/her desire, designated as nom-natural and irrational, heathen, effeminate, corrupted, lustful and concupiscent, as an heretical sex, puts on display the historical contingency of the homosexual subject typical of bourgeois capitalism since the ending of the nineteenth century.